Right ventricular myxoma infiltrating the tricuspid valve and obstructing the right ventricular inflow and outflow tracts - (:unkn) unknown (My University, 2000)
Myxomas originating in the right ventricle are extremely rare tumors. Herein, a case of right ventricular myxoma, infiltrating the tricuspid valve and causing right ventricular inflow and outflow tract obstruction, is described. Two-dimentional echocardiography diagnosed the mass easily and cardiac Doppler with color-flow examinations defined precisely its hemodynamic consequences to the heart. Magnetic resonance imaging study helped in preoperatively defining its intracardiac extension and the differential diagnosis by its very specific tissue characterization. The patient was successfully treated surgically and the tricuspid valve was replaced with a bioprosthesis because of tumor invasion of the valvular tissue.
Keywords: Myxoma; Right heart ventricle; Tricuspid valve; Ventricular inflow obstruction; Ventricular outflow obstruction